The good rain ebook Across time and terrain in the pacific northwest. - Egan, Timothy (Vintage Departures., 2011)
A fantastic book! Timothy Egan describes his journeys in the Pacific Northwest through visits to salmon fisheries, redwood forests and the manicured English gardens of Vancouver. Here is a blend of history, anthropology and politics.